The environmental cost of cryptocurrency: Analyzing CO2 emissions in the 9 leading mining countries - Mahsa Bashari; Saleh Ghavidel Doostkouei; Mehdi Fathabadi; Masoud Soufimajidpour (Sustainable Futures)
This study examines the environmental impact of cryptocurrency mining, specifically its contribution to CO2 emissions, in nine countries that account for 90% of global mining: the United States, China, Russia, Canada, Germany, Malaysia, Kazakhstan, Ireland, and Iran. Utilizing monthly panel data from 2019 to 2022 across nine countries and applying both pooled and fixed effects econometric techniques, the analysis reveals that ”energy intensity” (the amount of energy used to produce a unit of GDP), as a moderator variable, influences the effect of cryptocurrency mining on CO2 emissions. Specifically, in countries where the annual energy intensity growth rate is greater than −6%, cryptocurrency mining tends to result in higher CO2 emissions. Conversely, in countries with a growth rate of energy intensity below -6%, cryptocurrency mining results in lower CO2 emissions. The findings indicate that all nine countries experience a positive impact on CO2 emissions, albeit to varying degrees. The countries are categorized into three groups based on their performance: underperformers (Russia, the United States, Canada), neutral-effect countries (Iran, Kazakhstan, China), and positive performers (Ireland, Germany, Malaysia). This research underscores the urgent need for sustainable practices in cryptocurrency mining to mitigate its environmental effects.